Too beautiful to picture : Zeuxis, myth, and mimesis - Mansfield, Elizabeth (University of Minnesota Press, 2007)
Myth and Mimesis in western art history -- Art history as myth -- The Zeuxis myth -- Myth and Mimesis in the Renaissance -- Painting (like) Zeuxis -- Zeuxis in the academy -- Women artists and the Zeuxis myth -- Painting in the philosophical brothel -- Zeuxis in the operating room: Orlan's carnal art -- Conclusion: Zeuxis selecting models and the cultural unconscious